DATA SECURITY IN THE CLOUD: Study and Simulations - Adeyeye, Richard (My University, 2018)
Cloud technology is a nascent technology, thriving in information communication and data storage, and is still under development. Securing the communication links and data has been very paramount to the development of this technology and system. Various techniques, methods and technologies have been implemented in order to secure this system. Security of the cloud has recently witnessed much attention, as there have on-going research and studies towards the development of more potent solutions. Cryptography is one of the feasible and in demand solutions here, as it offers a set of security measures such as confidentiality, integrity and availability. This thesis work is aimed at understanding the data security in the cloud systems, and the various security threats associated with such technology. To better understand this, a thorough literature review is conducted on a cloud technology, and some of the cloud attacks are simulated. The distributed denial of service is simulated using NS3 and EstiNet, ARP poisoning is simulated using Ettercap, and the SQL injection is simulated using Damn Vulnerable Web Application. At the end of the task, the simulation scenarios were analyzed for better understanding and the observations were concluded. It was found out that these attacks are threat to the communication channels, network bandwidth, and the information being transferred. It was also realized that these attacks could be managed effectively using appropriate cryptographic techniques or technologies to block any unauthorised access to the network.
Keywords: cloud systems; cryptography; information security; cloud attacks; simulations; NS3; Et-tercap; EstiNet.; fi=Communications and System Engineering|en=Communications and System Engineering|; fi=Communications and System Engineering|en=Communications and System Engineering|